1990
DOI: 10.1007/bf01808107
|View full text |Cite
|
Sign up to set email alerts
|

Diketopiperazine-mediated peptide formation in aqueous solution

Abstract: Though diketopiperazines (DKP) are formed in most experiments concerning the prebiotic peptide formation, the molecules have not been paid attention in the studies of chemical evolution. We have found that triglycine, tetraglycine or pentaglycine are formed in aqueous solution of glycine anhydride (DKP) and glycine, diglycine or triglycine, respectively. A reaction of alanine with DKP resulted in the formation of glycylglycylalanine under the same conditions. These results indicate that the formation of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 25 publications
(20 reference statements)
5
32
0
Order By: Relevance
“…This was in agreement with previously reported results, that the formation of peptide bonds of triglycine, tetraglycine or pentaglycine from glycine anhydride and glycine, diglycine or triglycine respectively (glycine anhydride + (glycine) n → (glycine) n+2 ) proceed through the nucleophilic attack of an amino group of the amino acids or the oligoglycines on the glycine anhydride accompanied by the ringopening, thus the larger the number of n, the higher the yield of the resulting peptide 28 . Copolymerization of L-lactide with glycine anhydride was further studied using other catalysts.…”
Section: Resultssupporting
confidence: 93%
“…This was in agreement with previously reported results, that the formation of peptide bonds of triglycine, tetraglycine or pentaglycine from glycine anhydride and glycine, diglycine or triglycine respectively (glycine anhydride + (glycine) n → (glycine) n+2 ) proceed through the nucleophilic attack of an amino group of the amino acids or the oligoglycines on the glycine anhydride accompanied by the ringopening, thus the larger the number of n, the higher the yield of the resulting peptide 28 . Copolymerization of L-lactide with glycine anhydride was further studied using other catalysts.…”
Section: Resultssupporting
confidence: 93%
“…This phenomenon can be attributed to the intramolecular condensation of Ala [34], which proceeded readily because of the short distance between the amino and carboxyl groups of a single Ala molecule. Besides, the stereochemical feasibility of Ala made the intramolecular condensation much more readily [35,36]. It has been reported that the activation energy for the conversion of (Ala) 2 to DKP is significantly lower than that for the formation of (Ala) 2 from two Ala molecules, and the formation of DKP is preferred in most condensation reactions especially at relatively high temperature [37].…”
Section: Resultsmentioning
confidence: 99%
“…The carbamoylating agent is cyanate, formed from the urea (45). When a similar reaction was run in an open system to facilitate ammonia loss, half of the urea was destroyed after 5 hr at 90°C and pH 7 (46). Diglycine, oligoglycines, and diketopiperazines were other reaction products.…”
Section: ϫ5mentioning
confidence: 99%